OPTIMASI FORMULA TABLET LEPAS LAMBAT IBUPROFEN - Sumargo, Fredy; Hadisoewignyo, Lannie (Jurnal Farmasi Indonesia, 2011)
Ibuprofen was one type of antiinflammation drug that is often used so frequently in a day. Therefore, ibuprofen should be formulated in the form of sustained release tablet and find the optimum formula using factorial design. Factors used are a concentration of combination locust bean gum â?? xanthan gum matrix at 5% - 10% and concentration PVP K-30 at 3% - 5%. Preferred response Banakar follow the criteria was percent of dissolved drug in 3 hours at 25% - 50% and the percent of dissolved drug in 6 hours at 45% - 75%. The purpose of this study was to determine the effect of both factors and their interactions and get the optimum formula for the disposal of the following criteria Banakar. Concentration of combination xanthan gum-locust bean gum and concentration of PVP K-30 factor inhibit dissolved ibuprofen from tablets. While their interaction increase dissolved ibuprofen from tablet. Based on Design-Expert program optimation, optimum formula was obtained using a concentration of combination locust bean gum â?? xanthan gum matrix 7.58% and concentration of PVP K-30 3.09% would be result dissolved drug in 3 hours amounted to 49.3137% and dissolved drug in 6 hours amounted to 51.7607%. Â ABSTRAK Ibuprofen merupakan obat Â antiinflamasi yang digunakan dengan frekuensi penggunaan berulang kali dalam sehari. Oleh karena itu, ibuprofen perlu diformulasikan dalam bentuk lepas lambat dan dicari formula optimumnya dengan menggunakan metode factorial design. Faktor yang digunakan adalah faktor konsentrasi kombinasi matriks locust bean gum â?? xanthan gum pada konsentrasi 5% â?? 10% dan faktor konsentrasi PVP K-30 pada konsentrasi 3% - 5%. Respon yang dipilih mengikuti kriteria Banakar yaitu persen obat larut 3 jam 25 â?? 50% dan persen obat larut 6 jam 45 â?? 75%. Tujuan penelitian ini adalah mengetahui pengaruh kedua faktor dan interaksinya serta untuk memperoleh formula optimum yang pelepasannya mengikuti kriteria Banakar. Faktor konsentrasi kombinasi matriks locust bean gum â?? xanthan gum dan faktor konsentrasi PVP K-30 menghambat jumlah ibuprofen yang larut. Interaksi kedua faktor meningkatkan jumlah ibuprofen yang larut. Berdasarkan program optimasi Design Expert diperoleh formula optimum menggunakan konsentrasi kombinasi matriks xanthan gum-locust bean gum 7,5775% dan konsentrasi PVP K-30 3,09%,menghasilkan persen obat terlepas 3 jam sebesar 49,3137% dan persen obat terlepas 6 jam sebesar 51,7607%.